Programming, Profit Rates and Pricing Decisions. - Colantoni, Claude S.; Manes, Rene P.; Whinston, Andrew (The Accounting Review, 1969)
Abstract The article presents information on programming, profit rates and pricing decisions. Many, perhaps most, linear programming models whose objective is profit maximization assume a short run situation under conditions of perfect competition. The management techniques they develop serve as prescriptive guides to the solution of current operating problems and are devoid of any pricing considerations. It is true that fixed costs are usually lurking behind the set of constraints subject to which the 1.p. model is to be solved. The distinction between the 1.p. model under conditions of perfect competition or of monopoly has been pointed out. A full-cost pricing 1.p. model for price fixers has been explained. First, the 1.p. model for two activities and a constant markup was illustrated by Problem 1 and the implications for pricing considered. Next, the result of bid restrictions on activity levels was found to be that the full-cost model becomes an integer programming. Problem 2 was used to introduce the dual problem together with parametric analysis and to discuss planning and capital budgeting implications of the model. Finally, the difficulties arising where differential rates of return exist between activities were demonstrated by Problem 4.